HDI, Oil Prices, Government Expenditures in GCC: Evidence from a Cross Sectional ARDL Approach - Yasser, Mai; Salman, Doaa; Essam, Mohamed (Ekonomika, 2024)
This study explores the relationship between oil prices and the Human Development Index (HDI) in the Gulf Cooperation Council (GCC) countries. It investigates whether oil prices remain the primary driver of economic growth and development in the region. The analysis employs a Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) approach and Cointegrated Autoregressive Distributed Lag (CCEMG) methods, following unit root and stationarity tests. The findings reveal an insignificant correlation between oil prices and HDI in the overall GCC countries. However, significant relationships are observed at the individual country level. These results suggest that policymakers in the region should prioritize economic diversification and focus on sectors such as tourism in Dubai and the specific policies implemented in Saudi Arabia to foster sustainable development.